Literature study of millennial leadership concepts to find new perspectives on leadership styles - Kusumawati, Berlianingsih; Masduki, Uki; Utami, Sulistyo Seti; Dahlan, Dede; Maryama, Siti (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, Indonesia, 2023)
The leadership style was born driven by the assumption that the previous leadership style is no longer relevant if applied to today's millennial generation. This research is the first step to discovering millennial leadership styles that are difficult to find in previous literature. This study will use the literature review methodology to identify a range of theories that are pertinent to the issue under study. Data obtained from the Proquest and Google Scholar databases. The keywords leadership, leadership, leadership style, and millennial worker are used. We'll take the relevant article and analyze it, the article written between 2010–2022. This study find indicators of millennial leadership style based on the needs and characteristics of the millennial generation. There are eighteen indicators of millennial leadership style based on studies.